Gene expression profiles during embryo development in Brassica napus. Issue 5 (26th March 2013) - Venglat, Prakash; Xiang, Daoquan; Yang, Hui; Wan, Lianglu; Tibiche, Chabane; Ross, Andrew; Wang, Edwin; Selvaraj, Gopalan; Datla, Raju
Abstract: The seed in angiosperms is produced through coordinated development of the embryo, endosperm and seed coat. In dicots, most of the seed mass is taken up by the embryo with nutritional reserves stored in the cotyledons. During embryogenesis, well‐coordinated developmental and genetic programmes establish the embryonic body plan, and the associated complex metabolic pathways result in the production of diverse nutrients and deposition of important seed storage reserves. To gain insights into the genetic programmes that operate during embryo development in Brassica napus L. (canola), an important oilseed crop, we performed gene and protein expression analyses. We used the key stages from single‐cell zygote to mature embryo to generate comprehensive EST and proteome data sets. Analysis of these data sets identified 20 183 genes and 2607 proteins that are differentially expressed across different stages of embryo development. B. napus genes share high degree of homology with Arabidopsis and display stage‐specific and shared expression patterns associated with developmental and metabolic pathways. Together, this study has generated useful new molecular and genomic resources for embryo development in B. napus .